PENDEKATAN ISLAM DALAM RAWATAN DAN PEMULIHAN DADAH (NARKOBA) - Muhammad Khairi Mahyuddin (Jurnal Ushuluddin Adab dan Dakwah, 2018)
Drug abuse is a problem that causes addiction, health damage and social problems. It is a disease that can be treated and restored. In Islam every disease has its method and medicine. In the recovery of addiction and drug abuse. The Islamic approach is able to restore individuals from drugs. This writing explains the Islamic approach according to the Qur'an, the hadiths and the opinions of the Muslim muktabar. The outcome of the Islamic approach is comprehensive that embodies the aspects of the heart, emotion and physical. The success of drug rehabilitation through a religious approach depends on the extent of individuals holding, practicing and religious beliefs as a guide for survival to achieve happiness in the world and in the hereafter. Islam encourages taking the cause of musabbab for the recovery together with the healing of faith is coming from God.